An international comparison of childhood injuries in Hong Kong. Issue 1 (1st March 2000) - Chan, Charles C; Cheng, J C Y; Wong, T W; Chow, C B; Luis, Ben P K; Cheung, W L; Chan, Kevin
Abstract : Objectives —This study describes 7813 childhood injuries in Shatin, Hong Kong. Supplementary analyses include developmental specificity of external causes and comparison with international childhood injury data. Methods —Children aged 0–15 attending the accident and emergency (A&E) department of the Prince of Wales Hospital in Hong Kong were recruited for the study. Attendance records of participants from the A&E department were analyzed. Details concerning the injury, including the International Classification of Diseases, ninth revision, external cause of injury (E code), nature of injury (N code), abbreviated injury scale, and injury severity scale constitute core measurements, along with participants' age, gender, and respective A&E procedural data. Results —Males (65.7%) and fall related injuries (44.2%) predominate, while contusion (34.6%) is the prevailing nature of injury. Two age external cause dimensions are derived from a correspondence analysis. Children 0–1 years old are associated with falls, poisoning, scalds, and machinery related injury. Adolescents aged 12–15 are associated with motor related injury, animal related injury, and cuts/piercings. In comparison with international data, unintentional child injuries in Hong Kong comprised more falls but fewer poisonings and burns. Conclusion —A large proportion of falls, along with low proportion of poisonings and burns, are characteristics of childhood injury profile in Hong Kong. From the results of age external cause correspondence analysis, prevention strategies for different external cause should be developmentally specific.